Substitution of Metallocenes with [2.2]Paracyclophane to Enable Confocal Microscopy Imaging in Living Cells. Issue 2 (13th July 2016) - Skiba, Joanna; Schmidt, Claudia; Lippmann, Petra; Ensslen, Philipp; Wagenknecht, Hans‐Achim; Czerwieniec, Rafał; Brandl, Fabian; Ott, Ingo; Bernaś, Tytus; Krawczyk, Barbara; Szczukocki, Dominik; Kowalski, Konrad
Abstract : Bioimaging techniques that allow the visualization of ferrocene in living cells do not exist. This work addresses this challenging problem, and a new indirect approach for the bioimaging of ferrocenyl compounds in living and fixed cells is proposed. It is based on the structural similarity of metallocenyl (ferrocenyl and ruthenocenyl) groups to their metal‐free [2.2]paracyclophanyl congeners. Three adequately designed compounds were obtained. They share a 5‐(1‐ethynylpyrenyl)uracil group as a common structural motif and differ in their three‐dimensional aromatic substituents, namely, [2.2]paracyclophanyl, ferrocenyl and ruthenocenyl. The first substituent allows pyrenyl luminescence to occur, whereas the latter two act as quenchers. The accumulation of the luminescent derivative in the membranes, cytoplasm and mitochondria of living and fixed cells was confirmed by confocal microscopy. Microscopy studies were further correlated with high‐resolution continuum‐source atomic absorption spectroscopy (HR‐CS AAS) measurements of the ruthenocenyl compound that confirmed the uptake of ruthenium into the cells. Thus, taking into account the overall similarity of the compounds under study, it can be hypothesized that the metallocenyl derivatives are localized in the membranes, cytoplasm and mitochondria of the assayed cells. This is the basis for the more general concept of the utilization of luminescent [2.2]paracyclophanes as probes in indirect bioimaging studies of metallocene derivatives. Abstract : The biodistribution of metallocenyl uracil–pyrenes is investigated through an indirect approach that exploits the structural similarities of metallocenyl and [2.2]paracyclophanyl groups. Confocal microscopy of a [2.2]paracyclophane uracil–pyrene shows its accumulation in the membranes, cytoplasm, and mitochondria. A similar biodistribution pattern is postulated for the metallocenyl congeners.